SUMMONS TO COURT AND MEASURES TO ENSURE THE PARTICIPATION OF THE PARTIES IN THE JUDICIAL PROCESS IN RUSSIA IN THE SECOND HALF OF 17TH - BEGINNING OF THE 18TH CENTURIES - Levon Batiev (Гуманитарные и юридические исследования)
Traditional forms to ensure the participation of the defendant in court included summons according to "pristavnaya pamyat" (bailiff's sheet), "zazyvnaay gramota" (call charter), "nakaznaya pamyat" (call order), "privod" (summons) of the defendant by the plaintiff with the help of a guard, bringing in and detention of peasants in court, detention of "pravykh" (not guilty) in court, preferably the best peasants of the defendant. At the beginning of the 18th century according to "sysknaya" and "nakaznaya pamyat" (search and call orders) it was necessary not only to ind and provide the defendant on bail, but bring them to the court or to receive "srochnaya skazka" (urgent messege) and put the "pravykh" (not guilty) peasants on maintenance. Suspected peasants were supposed to be brought to the court by their landlords. In the "investigative process", including the military courts, the accused were sought after, arrested and escorted into the prison with the use of all possible military, police and other methods. Some soft forms were allowed for those of the upper classes or even for lower nobility. Guarantee (the main means of ensuring the participation of the parties in the court) accompanied all the proceedings in the role of guarantor of the execution of judgments and the admission of the tolls to the treasury. In the absence of guarantors the defendant or the plaintiff were transferred, despite the prohibition, upon "dobraya rospiska" (voluntary note) to a third party, or even detained. The timing of the trial (start, pause, resume, etc.) depended on the will of the parties. Failure to come in the time set or the period chosen by the parties, lead to a charge (claim loss) "bez suda" (without trial), in all cases, except for "krepostnykh" (serfs). The means of registration of participants' attendance upon a summoning was "stavochnaya" petition ("skazka", "stavka" or a note). At the end of 17th - beginning of the 18th centuries there was a simplification and tightening of forms and means of summons, restriction of freedom of the defendant (the freedom to avoid the court). Legal proceedings was becoming even less a private matter of the parties.